TRANSFORMASI PERKOTAAN MELALUI KOLABORATIVE GOVERNANCE DALAM PROGRAM TANGERANG GEMILANG BERBASIS SMART CITY - Retno Putri Fitriah; Rachma Fitriati (Journal Publicuho, 2023)
Smart City is considered to be an innovation in solving the complexity of urban problems, requiring cooperation between government, society, the private sector and stakeholders. This research aims to understand the collaboration process between various stakeholders carried out by the Tangerang Regency Government through the Tangerang Gemilang application in realizing the Smart City concept. Qualitative research methods with a case study strategy were used, and data was collected using literature studies, interviews and documentation. The research results explain that Tangerang Gemilang has succeeded in providing efficient and easily accessible public services via digital platforms. The Tangerang Gemilang application allows the public to access public information, submit requests, and report problems by reducing complicated permits and increasing transparency. Through a collaborative governance approach, this program involves several actors in decision making and policy implementation, including government, society and the private sector. Active community participation is realized through the use of applications as a communication channel between the community and the government. Collaborative Governance is an important foundation in improving the quality of Smart City-based urban services in Tangerang Regency.